The impact of Covid-19 and of the earlier crisis on firms' innovation and growth: A comparative analysis - Anabela Marques Santos; Karel Haegeman; Pietro Moncada Paternò Castello (European Commission, Joint Research Centre (JRC), 2021)
Using the results of the Survey on the Access to Finance of Enterprises (2009 to 2020 editions), this paper aims to assess the effect of Covid-19 pandemic on the probabilities of firm to innovate and grow and to compare their likelihood with that of the previous downturn. To control for a possible endogeneity bias as part of innovation decisions a Recursive Bivariate Probit Model is used. Results show that the probabilities of firms to innovate and grow are lower in 2020 (Covid-19 crisis) than in 2009 (financial crisis). The economic performance of innovative firms was also affected by the pandemic, but considerably less than the performance of non-innovative ones. Changes in the innovation patterns are also observed. Possible implications for decision-makers are derived.
Keywords: O31; O12; O52; 330; Innovation; Growth; Covid-19; Europe